Faktor – Faktor Yang Berhubungan Dengan Produktivitas Kerja Tenaga Kesehatan Di Puskesmas Tulang Bawang I Kabupaten Tulang Bawang - Suhartini Suhartini; M. Arifki Zainaro; M. Ricko Gunawan (Malahayati Nursing Journal, 2020)
ABSTRACT: FACTORS RELATED TO THE WORK PRODUCTIVITY OF HEALTH WORKERS AT THE TULANG BAWANG I HEALTH CENTER IN TULANG BAWANG REGENCY  Introduction: Based on data from the electric health information system (SIKDA) it is known that Puskesmas Tulang Bawang I, input data produced in 2017 were 27 reports, in 2018 there were 316 reports. At the 2017 Penawar Jaya Community Health Center there were 656 reports and in 2018 there were 788 reports, from the data reports it was seen that the Tulang Bawang I Health Center did not report activities to the fullest.Objective: known factors related to the work productivity of health workers at the Tulang Bawang I Health Center in Tulang Bawang Regency in 2019.Method: Type of quantitative research, research design with cross sectional approach. The population in this study were all health workers at the Tulang Bawang I Health Center in Tulang Bawang Regency with a sample of 63 people. There are two variables in this study, namely: Independent variables: motivation, work discipline and work ethic. The dependent variable in this study is work productivity. Analysis of data by univariate (frequency distribution) and bivariate using the chi square test.Results: It is known that respondents with good work productivity as many as 34 (54.0%) respondents, poor work discipline as many as 36 (57.1%) respondents, good motivation as much as 50 (50%) respondents, and good work ethic as many as 39 (61.9 %) respondents. There is a relationship between work discipline and work productivity of health workers (p-value = 0,000 OR 20,800). There is a correlation between motivation and work productivity of health workers (p-value = 0.005 OR 9.778). There is a relationship between work ethic and work productivity of health workers (p-value = 0.020 OR 4,000). Suggestions provide opportunities for employees to express ideas and innovations in the process of progress of the hospital by looking at the rules that apply in the hospital. Key Word:  work productivity, work discipline, motivation, work ethic   INTISARI: FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PRODUKTIVITAS KERJA TENAGA KESEHATAN DI PUSKESMAS TULANG BAWANG I KABUPATEN TULANG BAWANG  Pendahuluan: Berdasarkan data sistem informasi kesehatan daera (SIKDA) elektrik diketahui bahwa Puskesmas Tulang Bawang I, input data yang dihasilkan tahun 2017 sebanyak 27 laporan, di tahun 2018 sebanyak 316 laporan. Pada Puskesmas Penawar Jaya tahun 2017 sebanyak 656 laporan dan di tahun 2018 sebanyak 788 laporan, dari laporan data terlihat bahwa Puskesmas Tulang Bawang I tidak melaporkan kegiatan dengan maksimal.Tujuan : diketahui faktor – faktor yang berhubungan dengan produktivitas kerja tenaga kesehatan di Puskesmas Tulang Bawang I Kabupaten Tulang Bawang  tahun 2019.Metode : Jenis penelitian kuantitatif, rancangan penelitian dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah seluruh petugas kesehatan  di Puskesmas Tulang Bawang I Kabupaten Tulang Bawang dengan sampel 63 orang. Variabel dalam penelitian ini ada dua yaitu: Variabel independen: motivasi, disiplin kerja dan etos kerja. Variabel dependen dalam penelitian ini adalah produktivitas kerja. Analisa data secara univariat (distribusi frekuensi) dan bivariat menggunakan uji chi square.Hasil Penelitian : Diketahui responden dengan produktivitas kerja baik sebanyak 34 (54,0%) responden, disiplin kerja kurang baik sebanyak 36 (57,1%) responden, motivasi baik sebanyak 50 (50%) responden, dan etos kerja baik sebanyak 39 (61,9%) responden. Ada hubungan disiplin kerja dengan produktivitas kerja tenaga kesehatan (p-value = 0,000 OR 20,800). Ada hubungan motivasi dengan produktivitas kerja tenaga kesehatan ( p-value = 0,005 OR 9,778). Ada hubungan etos kerja dengan produktivitas kerja tenaga kesehatan (p-value = 0,020 OR 4,000). Saran memberikan kesempatan pada pegawai untuk mengungkapkan ide dan inovasi dalam proses kemajuan rumah sakit dengan memandang aturan yang berlaku di rumah sakit. Kata kunci    : produktivitas kerja, disiplin kerja, motivasi, etos kerja